Association of Life’s Essential 8 Score with All-Cause and Cardiovascular Mortality in Patients with Diabetic Nephropathy: A NHANES-Based Cohort Study - Zhang F; Li W (Journal of Multidisciplinary Healthcare, 2025)
Fan Zhang,1,2 Wenjian Li3,4 1Department of Endocrinology, Changzhou Third People’s Hospital, Changzhou, Jiangsu, People’s Republic of China; 2Department of Clinical Nutrition, Changzhou Third People’s Hospital, Changzhou, Jiangsu, People’s Republic of China; 3Department of Urology, Changzhou Third People’s Hospital, Changzhou, Jiangsu, People’s Republic of China; 4Changzhou Clinical College, Xuzhou Medical University, Changzhou, Jiangsu, People’s Republic of ChinaCorrespondence: Wenjian Li, Department of Urology, Changzhou Third People’s Hospital, 300 Lanling North Road, Changzhou, Jiangsu, 213001, People’s Republic of China, Tel +86-0519-82009011, Email bolite@163.comPurpose: This study aimed to assess the relationship between the “Life’s Essential 8” (LE8) score and all-cause and cardiovascular mortality in patients with diabetic nephropathy (DN).Methods: This observational cohort study utilized data from the National Health and Nutrition Examination Survey (NHANES, 2005– 2018). A total of 1,745 patients with DN were included. The LE8 score encompassed health behaviors (diet, physical activity, nicotine control, sleep) and physiological indices (body mass index, non-high-density lipoprotein cholesterol, blood glucose, blood pressure). A multivariate Cox proportional risk model was employed to assess the effect of the LE8 score on the risk of death, and the dose-response relationship was analyzed by a restricted cubic spline (RCS) model. Subgroup analyses and multiple imputations were performed to verify the robustness of the findings.Results: After adjusting for confounders, a 10-point increase in the LE8 score was associated with a 12% reduction in the risk of all-cause mortality [hazard ratio (HR) = 0.88, P < 0.001] and a 16% reduction in the risk of cardiovascular death (HR = 0.84, P = 0.007). The risk of all-cause mortality was 33% lower in the highest tertile group compared with the lowest group (HR = 0.67, P < 0.001), and the risk of cardiovascular mortality was 36% lower (HR = 0.64, P = 0.014). RCS analysis showed that LE8 scores were linearly negatively correlated with mortality (nonlinear P > 0.05). Subgroup analyses further confirmed the consistency of this association across various characteristic subgroups.Conclusion: LE8 score has been identified as an independent protective factor for the risk of death in patients with DN, exhibiting a linear dose-response relationship consistent across sociodemographic subgroups. This finding underscores the importance of incorporating LE8 into a comprehensive assessment system for DN patients, providing a foundation for precision intervention.Keywords: diabetic nephropathy, life’s essential 8, all-cause mortality, cardiovascular mortality, cohort studies